L' "Unum Argumentum" di Anselmo nella Riflessione Cistercense del XII Secolo, Teil 1, Aelredo di Rievaulx e Isacco della Stella - Zoppi, Matteo (Lateranum, 2024)
The paper is divided in two parts: the first studies the receptions of Proslogion's unum argumentum in the Anglo-Saxon Cistercian tradition, the second in the continental tradition, by authors who have often acquired, interpreted and reformulated it in order to promote their spiritual quest, through new suggestions related to their radical monastic spirituality, Areopagitic apophaticism and the return to classical and Patristic tradition.